Florida Production Budgets and Agribusiness Analysis - Scott A. Smith (EDIS)
FE688, a 5-page document by Scott A. Smith, presents access information and a listing of production budgets for livestock and the following crops: citrus, field, forage, fruit and nuts, tropical fruits and vegetables, and vegetables. Also included is a web link to a business analysis of ornamental plant nurseries for various areas of Florida. Published by the UF Department of Food and Resource Economics, May 2007.